Hydrodynamic simulations of terahertz oscillation in double-layer graphene *Project supported by the National Natural Science Foundation of China (No. 11604126). (December 2018) - Feng, Wei
Abstract: We have theoretically studied current self-oscillations in double-layer graphene n+nn+ diodes driven by dc bias with the help of a time-dependent hydrodynamic model. The current self-oscillation results from resonant tunneling in the double-layer graphene structure. A detailed investigation of the dependence of the current self-oscillations on the applied bias has been carried out. The frequencies of current self-oscillations are in the terahertz (THz) region. The double-layer graphene n + nn + device studied here may be presented as a THz source at room temperature.